MENINGKATKAN HASIL BELAJAR MATEMATIKA (OPERASI PENJUMLAHAN) MELALUI PENDEKATAN REAL BAGI ANAK BERKESULITAN BELAJAR KELAS I DI SDN 07 SALIDO - Karlina - (Jurnal Penelitian Pendidikan Khusus, 2014)
This research was motivated by the bermasalahan one cause of children learning mathematics very closely berkesuiltan his relationship with the child's social and environmental factors . As where the author met in first grade students of SD Negeri 07 Salido market the majority of students live on the beach . They are forced to work to help their parents to cover the needs of the economy . At an early age they have to work to dry their fish sometimes even locked up at home to care for younger brother . Though they really need time to play and socialize with the surrounding environment .